The Principal’s Strategy in Optimizing Learning Communities for the Pedagogical Competency Development of Kindergarten Teachers - Sa'adah, Anis; Hariyati, Nunuk; Haq, Mohammad Syahidul; Khamidi, Amrozi; Nursalim, Mochamad (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
The title of this research is the principal's strategy in optimizing the learning community for the development of teacher pedagogical competence in kindergarten. There are two research objects, namely the principal's strategy and the pedagogical competence of teachers in kindergarten. The aim of this research is to describe the principal's strategy in optimizing the learning community to develop teacher pedagogical competence in kindergarten. The type of research is qualitative descriptive research which uses interviews, observation and documentation to collect data. Respondents involved school administrators, principals, teachers and education staff at the two schools. The research results show that the strategies used by school principals in developing teacher pedagogical competence include: forming small teams, setting routine schedules, implementing collaboration, and creating an environment that supports sustainable learning. This strategy has proven to be effective in developing teacher competence in designing, implementing and evaluating learning. However, this strategy is not without obstacles, among the obstacles faced are related to time, facilities, and the school community's resistance to change.